Whatever It Takes: How and When Supervisor Bottom-Line Mentality Motivates Employee Contributions in the Workplace - Babalola, Mayowa T.; Mawritz, Mary B.; Greenbaum, Rebecca L.; Ren, Shuang; Garba, Omale A. (Journal of management, 2021)
Given that many organizations are competitive and finance centered, organizational leaders may lead with a primary focus on bottom-line attainment, such that they are perceived by their subordinates as having a bottom-line mentality (BLM) that entails pursuing bottom-line outcomes above all else. Yet, the field is limited in understanding why such a leadership approach affects employees’ positive and negative contributions in the workplace. Drawing on social exchange theory, we theorize that supervisors high in BLM can influence employees’ felt obligation toward the bottom line, which in turn can influence employees’ task performance and unethical pro-organizational behavior (UPB). We also examine employee ambition as a moderator of this process. Using three-wave, multisource data collected from the financial services industry, our results revealed that high-BLM supervisors elevate employee task performance as well as UPB by motivating employees’ felt obligation toward the bottom line. Furthermore, we found that employee ambition served as a first-stage moderator, such that the mediated relationships were stronger when employee ambition was high as opposed to low. Our findings break away from the dominant dysfunctional view of BLM and provide a more balanced view of this mentality.